BRAIN METASTASIS FROM HEPATOCELLULAR CARCINOMA: A RARE CASE - A. Kh. Bekyashev; N. V. Sevyan; D. M. Belov; A. V. Zotov; Yu. V. Tsybulskaya; D. R. Naskhletashvili (Опухоли головы и шеи, 2015)
Hepatocellular carcinoma ranks 5th in prevalence and 3rd in cancer mortality worldwide. The prognosis of this disease is very poor: the 5-year survival rate was not more than 3–5%. Metastases generally occur in the lung, in the lymph nodes of the abdomen, chest, and neck, in the vertebrae, kidneys, and adrenals. The cases of brain metastasis from hepatocellular cancer are very rare. Overall, the prognosis is very poor for patients with brain metastases from hepatocellular carcinoma. Nevertheless, solitary brain metastases and good hepatic function are favorable survival criteria; thus, the treatment of this group of patients may lead to their better survival. The paper describes a clinical case of brain metastasis from hepatocellular carcinoma in a patient receiving the combination treatment involving neurosurgical treatment and targeted therapy.